David and Goliath: dismantling inequalities within faith-based cross-sector partnerships. Issue 7 (2nd October 2016) - Sanders, Tonya
ABSTRACT: This article reports on a research project that explored the internal dynamics of a faith-based and cross-sector partnership when different levels of organisational resources and capacity exist. A case of a three-way partnership between a faith-based, a for-profit, and a non-profit organisation is analysed. Through participant observation, interviews, and an examination of secondary data using grounded theory and the constant comparison method of analysis, an assessment of how resources impacts partnership structure, agenda/goal setting, roles, and responsibilities are highlighted and framed to demonstrate the inequalities in partnership outcomes. Furthermore, a framework for how to infuse structural equality into these partnerships is discussed.